Body Mass Index and Association With Caries in School-Aged Children With Orofacial Cleft: A Case-Control Study. (February 2020) - Sundell, Anna Lena; Nilsson, Anna-Karin; Marcusson, Agneta; Törnhage, Carl-Johan
Objective: Data on the association between body mass index (BMI) and dental caries in children with orofacial clefts are sparse. Therefore, studies on the impact of BMI on caries frequency in children with cleft lip and/or palate (CL/P) are of importance. The aim of the current study was to investigate the association between BMI and frequency of dental caries in children with and without CL/P. Height, weight, and BMI in children with CL/P were also compared to controls. Design: This study used a cross-sectional case-control design. Participants: One hundred and thirty-nine 5- and 10-year-old children with CL/P and 299 age-matched controls. Main Outcome Measures: Caries was recorded according to the International Caries Detection and Assessment System. Height and weight were recorded, and BMI was calculated as weight/height 2 . Results: There was no correlation between BMI and caries frequency. Weight, height, and BMI were significantly lower in all children with CL/P compared to controls. After adjustment for international adoption, only BMI was significantly lower in CL/P children compared to controls. Non-adopted children with CL/P were significantly heavier and longer than adopted children with CL/P. Conclusions: Five- and 10-year-old children with corrected CL/P seemed to have a lower BMI than controls, but there was no association between BMI and caries frequency. Internationally adopted children with CL/P were lighter and shorter than non-adopted CL/P children and controls.